Subdural evacuating port system with subdural thrombolysis for the treatment of chronic subdural hematoma in patients older than 80 years - Liu, Tianqing; Gao, Zhenwen; Zhou, Jianjun; Lai, Xiaoyan; Chen, Xiaomei; Rao, Qiong; Guo, Dongbin; Zheng, Jinliang; Lin, Fuxin; Lin, Yuanxiang; Lin, Zhiqin (Frontiers in Neurology, 2023)
Objective The subdural evacuating port system (SEPS) is a minimally invasive approach that can be performed under local anesthesia for the treatment of chronic subdural hematoma (CSDH). Subdural thrombolysis has been described as an exhaustive drainage strategy and found to be safe and effective for improving drainage. We aim to analyze the effectiveness of SEPS with subdural thrombolysis in patients older than 80 years. Method Consecutive patients aged ≥80 years old who presented with symptomatic CSDH and underwent SEPS followed by subdural thrombolysis between January 2014 and February 2021 were retrospectively studied. Outcome measures included complications, mortality, recurrence, and modified Rankin Scale (mRS) scores at discharge and 3 months. Results In total, 52 patients with CSDH in 57 hemispheres were operated on, with a mean age of 83.9 ± 3.3 years, and 40 (76.9%) patients were men. The preexisting medical comorbidities were observed in 39 patients (75.0%). Postoperative complications occurred in nine patients (17.3%), with two having significant complications (3.8%). The complications observed included pneumonia (11.5%), acute epidural hematoma (3.8%), and ischemic stroke (3.8%). One patient experienced contralateral malignant middle cerebral artery infarction and died of subsequent severe herniation, contributing to a perioperative mortality rate of 1.9%. Discharge and 3 months of favorable outcomes (mRS score 0–3) were achieved in 86.5% and 92.3% of patients, respectively. CSDH recurrence was observed in five patients (9.6%), and repeat SEPS was performed. Conclusion As an exhaustive drainage strategy, SEPS followed by thrombolysis is safe and effective with excellent outcomes among elderly patients. It is a technically easy and less invasive procedure with similar complications, mortality, and recurrence rates compared with burr-hole drainage in the literature.